2019
DOI: 10.1126/science.aay6826
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Rome: A genetic crossroads of Europe and the Mediterranean

Abstract: Ancient Rome was the capital of an empire of ~70 million inhabitants, but little is known about the genetics of ancient Romans. Here we present 127 genomes from 29 archaeological sites in and around Rome, spanning the past 12,000 years. We observe two major prehistoric ancestry transitions: one with the introduction of farming and another prior to the Iron Age. By the founding of Rome, the genetic composition of the region approximated that of modern Mediterranean populations. During the Imperial period, Rome’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
268
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(300 citation statements)
references
References 101 publications
30
268
1
1
Order By: Relevance
“…In addition, we found present-day Sardinian individuals sit within the broad range of ancestry observed in our ancient samples. A similar pattern is seen in Iberia 14 and central Italy 54 , where variation in individual ancestry increased markedly in the Iron Age, and later decreased until present-day. In terms of the fine-scale structure within Sardinia, we note the median position of modern individuals from the central regions of Ogliastra and Nuoro on the main PCA ( Fig.…”
Section: S S Se Se S S a A A A A A A A E Se E E E E E E E E E Se S A Asupporting
confidence: 68%
“…In addition, we found present-day Sardinian individuals sit within the broad range of ancestry observed in our ancient samples. A similar pattern is seen in Iberia 14 and central Italy 54 , where variation in individual ancestry increased markedly in the Iron Age, and later decreased until present-day. In terms of the fine-scale structure within Sardinia, we note the median position of modern individuals from the central regions of Ogliastra and Nuoro on the main PCA ( Fig.…”
Section: S S Se Se S S a A A A A A A A E Se E E E E E E E E E Se S A Asupporting
confidence: 68%
“…Previous aDNA studies have used Beagle 4.0 to impute ancient genomes 10 13 , which accepts genotype likelihood input to estimate genotypes at all sites in the reference panel in a single step. Another imputation tool recently developed for low-coverage sequencing data, GLIMPSE, functions in a similar way 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we recommend using imputed genomes for downstream analyses incorporating genome-wide markers segregating at relatively high frequencies. They have been used in population genetics studies for detecting runs of homozygosity and identical-by-descent segments, and local ancestry deconvolution 10 13 , 25 . It has also been shown that low-coverage sequencing combined with imputation is more cost-effective in GWAS and generating polygenic risk scores 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…3). The only archaeological cluster (defined in annotations from the source dataset, modified for readability) with more than two individuals is 'Iron Age Republican Rome', where 3 of 11 samples reported in Antonio et al (2019) fall above the long ROH threshold. In the Pontic-Caspian Steppe region, 3 of 54 individuals who lived between 2,600-1,500 BP (5.6%, CI: 1.2-15.4%) exceed the threshold (Fig.…”
Section: Low Abundance Of Long Rohmentioning
confidence: 99%